2014
DOI: 10.1247/csf.13020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PKD in Cell Polarity, Biosynthetic Pathways, and Organelle/F-actin Distribution

Abstract: ABSTRACT. Protein Kinase D (PKD) 1, 2, and 3 are members of the PKD family. PKDs influence many cellular processes, including cell polarity, structure of the Golgi, polarized transport from the Golgi to the basolateral plasma membrane, and actin polymerization. However, the role of the PKD family in cell polarity has not yet been elucidated in vivo. Here, we show that KO mice displayed similar localization of the apical and basolateral proteins, transport of VSV-G and a GPI-anchored protein, and similar locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…As in other tissues shown (Atik et al, 2014), PKD1 and PKD2 were absent in the brains of PKD1 geo/geo (PKD1 KO) mice and PKD2 geo/geo (PKD2 KO) mice, respectively (Fig. 1A).…”
Section: Expression Of Pkd1 and Pkd2 In Brain And Hippocampal Neuronssupporting
confidence: 67%
See 3 more Smart Citations
“…As in other tissues shown (Atik et al, 2014), PKD1 and PKD2 were absent in the brains of PKD1 geo/geo (PKD1 KO) mice and PKD2 geo/geo (PKD2 KO) mice, respectively (Fig. 1A).…”
Section: Expression Of Pkd1 and Pkd2 In Brain And Hippocampal Neuronssupporting
confidence: 67%
“…Our previous work showed that PKD1 and PKD2 were expressed in various tissues, including the brain (Atik et al, 2014). As in other tissues shown (Atik et al, 2014), PKD1 and PKD2 were absent in the brains of PKD1 geo/geo (PKD1 KO) mice and PKD2 geo/geo (PKD2 KO) mice, respectively (Fig.…”
Section: Expression Of Pkd1 and Pkd2 In Brain And Hippocampal Neuronsmentioning
confidence: 78%
See 2 more Smart Citations
“…Data obtained in MEFs from mice deficient in PKD2 enzymatic activity (PKD2 S707A/S711A knock-in mutation (35,36)) further confirmed that the active kinase is indeed required for proper secretion of endogenous MMP2 cargo (Fig. 1, F and G), a function that has been also recently challenged (48). Thus, the PKD2-ARF1 protein complex is a critical dual regulator of vesicle formation and scission at the TGN during constitutive secretory processes.…”
Section: Discussionmentioning
confidence: 54%